2013
DOI: 10.3354/dao02638
|View full text |Cite
|
Sign up to set email alerts
|

Small leucine-rich proteoglycans in the vertebrae of Atlantic salmon Salmo salar

Abstract: We analysed the distribution and expression of the small leucine-rich proteoglycans (SLRPs) decorin, biglycan and lumican in vertebral columns of Atlantic salmon Salmo salar L. with and without radiographically detectable deformities. Vertebral deformities are a reoccurring problem in salmon and other intensively farmed species, and an understanding of the components involved in the pathologic development of the vertebrae is important in order to find adequate solutions to this problem. Using immunohistology a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…As with many of the other network genes, Lum is an ECM component and affects collagen fibril formation [89]. In Atlantic salmon, Lum is expressed at sites of endochondral and intramembranous ossification [90] and is a component of developing bone tissue in other vertebrate species [89], similarly to many of the other network genes. However, Lum is also a major proteoglycan in the cornea and sclera [91, 92], where it is likely to be independently regulated.…”
Section: Discussionmentioning
confidence: 99%
“…As with many of the other network genes, Lum is an ECM component and affects collagen fibril formation [89]. In Atlantic salmon, Lum is expressed at sites of endochondral and intramembranous ossification [90] and is a component of developing bone tissue in other vertebrate species [89], similarly to many of the other network genes. However, Lum is also a major proteoglycan in the cornea and sclera [91, 92], where it is likely to be independently regulated.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we demonstrated an up-regulation of biglycan mRNA during development from 2 to 15 g. Biglycan is reported to control signalling pathways regulating the osteogenic program (Berendsen et al 2011 ), and in vitro studies have demonstrated a different influence of biglycan and decorin on mineralization (Mochida et al 2003 ). A changed mRNA expression of decorin and biglycan has previous been demonstrated in salmon of 15 g size with vertebral deformities (Pedersen et al 2013 ). Thus, the presence of four sulphated DS in the notochord during growth and development of salmon is most likely a prerequisite for proper development, but further studies are needed to explore the consequences of the differences in biglycan and decorin expression in vertebral development.…”
Section: Discussionmentioning
confidence: 70%
“…In our study, C-6-S did not co-localize with KS in the chordocytes, suggesting the presence of other KS PGs. In a recent study, we immunolocalized lumican in the chordocytes of Atlantic salmon (Pedersen et al 2013 ). Lumican is reported to carry KS also in teleosts such as Atlantic cod (Tingbo et al 2012 ) and zebrafish (Souza et al 2007 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation